The effect of morality meters on ethical decision making in video games: A quantitative study. (May 2023) - Ryan, Malcolm; McEwan, Mitchell; Formosa, Paul; Messer, Jane; Howarth, Stephanie
Abstract: The "morality meter" is a popular mechanic in games involving ethical decision making used to give players moral feedback about their actions. However, this function is controversial, with some theorists claiming such meters reduce complex ethical problems to an artificial binary of 'Good' vs 'Evil' and encourage an instrumental approach to moral decision making. In this paper, we set out to empirically evaluate the effect of adding a morality meter to a simple visual-novel game involving a variety of ethical choices. Three different versions of the meter were tested and compared against a meter-free version of the game. Results show that the meter is generally ignored when the moral choice is straightforward, however it can influence decisions when the choice is morally ambiguous. The strength of the effect depends on the apparent trustworthiness of the meter. A meter which advocates intuitively immoral responses as Good has less influence than one that broadly aligns with the player's expected moral compass. Highlights: Morality meters in videogames can affect players' choices on ethical decisions when the ethical alternative is unclear. A meter advocating immoral responses has less influence than one that aligns with the player's moral compass. Players ignore the meter when morals choices are straightforward.